Aplikasi Persamaan Bessel Orde Nol Pada Persamaan Panas Dua Dimensi - Mulyati, Annisa Eki; Sugiyanto, Mr. (Jurnal Fourier, 2013)
Bessel differential equation is one of the applied equation in physics is about heat transfer. Application of modified Bessel function of order zero on heat transfer process of two-dimensional objects which can be modelled in the form of a two-order partial differential equations as follows, ..... With the obtained solutions of Bessels differential equation application of circular fin, .... Â  two-dimensional temperature stated on the point .....Â  against time t